Circular and transformative economy: advances towards sustainable socio-economic transformation - Nhamo, L.; Mpandeli, S.; Liphadzi, S.; Mabhaudhi, Tafadzwanashe (CRC Press, 2024)
The main aim of this book is to illustrate circular models for sustainable resource management. It highlights the benefits of transformative approaches in integrating, simplifying, and facilitating understanding of complex systems and transforming systems towards greater sustainability while achieving multiple social, economic, and environmental outcomes. It provides pathways towards strategic policy decisions on socio-economic transformation supported by case studies.